Ultrafast Phenomena XIX : Proceedings of the 19th International Conference, Okinawa Convention Center, Okinawa, Japan, July 7-11, 2014 /: Proceedings of the 19th International Conference, Okinawa Convention Center, Okinawa, Japan, July 7-11, 2014. (2015) - Unknown
No abstract available